UNLOCKING COMMUNITY INVOLVEMENT IN TOURISM: HOW SOCIO-ECONOMIC BENEFITS AND ETHICAL TOURIST BEHAVIOUR DRIVE SATISFACTION AND POSITIVE WORD-OF-MOUTH (Qualitative Research Journal for Social Studies, 2025)
This research aims to examine how residents' perceived socio-economic benefits influence community satisfaction, which in turn is expected to predict community involvement and positive word of mouth (WOM) about tourism. Drawing on Social Exchange Theory, this study also investigates tourist ethical behavior as a moderating factor. To empirically test the proposed model, a survey was conducted, and data were collected from 341 residents of Gilgit-Baltistan, the most visited tourist destination in Pakistan. The findings suggest that perceived socio-economic benefits positively impact community satisfaction, which subsequently leads to increased community involvement and positive WOM about tourism. Furthermore, tourist ethical behavior was also found to influence residents’ involvement and WOM intentions. Present research provides the completely understanding of the pivotal role community satisfaction plays in fostering community engagement and the promotion of tourist destinations. It underscores the importance of place-based and resident-informed policymaking for sustainable tourism development.